Sex Disparities of Genomic Determinants in Response to Immune Checkpoint Inhibitors in Melanoma - Shi, Fuyan; Zhang, Wenjing; Yang, Yichen; Yang, Yitao; Zhao, Junyi; Xie, Mengqi; Sheng, Chao; Wang, Suzhen; Wang, Qinghua (Frontiers in Immunology, 2021)
Background: Despite the acknowledged sex-related differences in immune response and immune checkpoint inhibitor (ICI) efficacy, little is known about the sex disparities in melanoma of novel genomic determinants for ICI therapies. Methods: Pre-treatment genomic profiles and clinical characteristics of 631 melanoma patients treated with ICIs (i.e., inhibitors of CTLA-4, PD-1/PD-L1, or both) were comprehensively curated. Genomic factors, i.e., significantly mutated genes (SMGs), mutational signatures, and molecular subtypes were identified and their associations with ICI treatment efficacy in male and female patients were evaluated. Results: Of the 15 SMGs identified in this study, three genes (i.e., CFH, DGKG, and PPP6C) were found to exhibit sex differences with respect to ICI efficacy. Among these, CFH mutations exhibited both response rate and survival benefits in male, but not in female patients. A total of four mutational signatures (i.e., signatures 1, 4, 7, and 11) were extracted. Male patients with signature 4 (also known as smoking-related signature) had an inferior ICI response rate and overall survival. However, this association was not significant in females. An immune subtype based on mutational activities was found to be significantly associated with poor ICI survival in female patients. Conclusion: We uncovered several sex-dependent genomic correlates of response to ICI treatment, such as male-biased CFH mutations and signature 4, and the female-biased immune resistance subtype. The findings derived from this research provide clues for exploring different immunotherapeutic approaches in male and female patients with melanoma.